Calculus early transcendental functions - Smith, Robert T. (Robert Thomas) 1955- (McGraw-Hill, 2012)
A critical course for science, technology, engineering and math majors. Reflects the three critical components of calculus success as identified by calculus faculty: mastery of prerequisited algebra and trignometry skills; clear and elegant presentation of calculus concepts; and the inclusion of classic calculus problems.